Dense composite electrolytes of Gd3+-doped cerium phosphates for low-temperature proton-conducting ceramic-electrolyte fuel cells. Issue 3 (April 2015) - Singh, Bhupendra; Kim, Ji-Hye; Park, Jun-Young; Song, Sun-Ju
Abstract: Dense Gd 3+ -doped cerium pyrophosphate–phosphate (CGP–P) composites are prepared by infiltrating H3 PO4 into partially sintered CGP substrates and then heat-treating at 375–400 °C. The phase composition and microstructure of CGP–P composites are studied by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM), which shows that the H3 PO4 reacts with CGP to form phosphate phases in the pores and results in a dense CGP–P composite. The ionic conductivity of CGP–P composite is studied by electrochemical impedance spectroscopy (EIS) in dry and humid atmosphere in 90–230 °C range for its application as electrolyte in proton-conducting ceramic-electrolyte fuel cells (PCFCs). It is observed that the ionic conductivity of the composite GCP–P-1h/375, formed by 1 h acid-treatment followed by heat-treatment at 375 °C, is 2.73×10 −6 S cm −1 at 230 °C in unhumidified air but in humidified air (water vapor pressure, p H2 O=0.12 atm) it shows a maximum of 0.051 S cm −1 at 170 °C, which is significant for its application as electrolyte in PCFCs.